Ferrocene thiazolidine-2,4-dione derivatives cause DNA damage and interfere with DNA repair in triple-negative breast cancer cells - Nyeleti Vukea; Ogunyemi Oderinlo; Matshawandile Tukulula; Setshaba David Khanye; Adrienne Lesley Edkins; Jo-Anne de la Mare (PLoS ONE, 2025)
In this study, ferrocene-containing thiazolidine-2,4-dione derivatives were screened against triple-negative breast cancer (TNBC) cell lines, which represent an aggressive subtype of the disease predominant in women of African descent. The lack of key receptors in TNBC poses a therapeutic challenge as there are limited targeted treatment options available for this subtype. The ferrocene thiazolidine-2,4-dione derivatives displayed toxicity against HCC70 TNBC cells in the low-moderate micromolar range (5–46 μM) and two compounds were selected for further study, with IC50 values of 7.54 ± 1.07 μM (OY25) and 5.59 ± 1.24 μM (OY29). Additionally, compounds OY25 and OY29 were screened against other cancer and non-tumourigenic cell lines and found to be less toxic against non-cancerous breast epithelial cell line MCF-12A (SI = 2.2188 and 4.4359, respectively) compared to the HCC70 TNBC cell line. Compounds OY25 and OY29 show a dual mode of action involving increased reactive oxygen species generation and induction of DNA damage. In silico docking analysis and competitive DNA binding fluorescence-based assays revealed that the compounds disrupt key DNA damage phosphoprotein levels through binding to the minor groove of DNA. In a combination assay, the compounds acted synergistically and antagonistically with DNA damage-inducing drugs, camptothecin and etoposide, respectively. Meanwhile, in combination with PARP-1 inhibitor, OY25 and OY29 acted synergistically and antagonistically, respectively. Furthermore, in silico results, using the SwissADME web tool, showed that the compounds OY25 and OY29 display desirable ADME (absorption, distribution, metabolism, and excretion) profile with parameters within acceptable range.